Mycotoxin production by three different toxigenic fungi genera on formulated abalone feed and the effect of an aquatic environment on fumonisins - Mariska Riana Greeff-Laubscher (Mycology, 2020)
Mycotoxins are toxic secondary metabolites produced by various filamentous fungi, of which Fusarium, Aspergillus and Penicillium are the three main genera. Fusarium verticillioides is one of the most dominant toxigenic fungal species, associated with fumonisin contamination in grain-based feeds, such as compound abalone feed. Mycotoxin production is influenced by temperature and available nutrients. In this study the aims were: to determine if abalone feed as growth substrate favours mycotoxin production for toxigenic fungi; to determine the most effective temperature for fumonisin production by F. verticillioides on abalone feed; and to assess the effect of the aquatic environment on fumonisin-contaminated abalone feed. A total of 93 fungal isolates were inoculated onto abalone feed, including species belonging to the genera Fusarium, Aspergillus and Penicillium. Feed inoculated with F. verticillioides were incubated at two different temperatures and fumonisin-contaminated feed was submerged into seawater for 24 h. Results showed that mycotoxins were produced when abalone feed was inoculated with toxigenic fungi, and that F. verticillioides produced higher concentrations of fumonisins at a lower temperature. Submerging fumonisin-contaminated feed in seawater showed that this toxin leached into the seawater, lowering the risk of fumonisins to be consumed by abalone.